Potret Curriculum Portrait Independent Learning At The Center Of Excellence School : (Study cases SMK Ma'arif NU Tirto Pekalongan) - Khobir, Abdul; Chonitsa, Ana; Chorida Adila, But (Jurnal Edusci, 2024)
In education, the curriculum is the main aspect of the learning process. The independent learning curriculum is categorized as a Center of Excellence school for vocational schools and a Driving School for high schools. However, this research focuses on vocational schools categorized as Center of Excellence schools. This study uses a qualitative method approach with field study research at SMK Ma'arif NU Tirto Pekalongan. The purpose of the research is to find out how the learning system in the Center of Excellence schools implements the Independent Learning Curriculum. Vocational Secondary Schools implementing the Merdeka Learning curriculum include the term P5BK (Pancasila Student Profile Strengthening and Work Culture Project) in each subject. Therefore, school principals, teachers, and students must be ready to implement the Independent Learning curriculum. For PK vocational schools in Pekalongan, the level of readiness is mature and according to the criteria of the Ministry of Education. This can be seen from the supporting factors, which include synchronization between teachers and students regarding the concept of the Independent Learning Curriculum, teachers as facilitators of student learning, and the encouragement of counseling guidance teachers for students and many young teachers who can utilize technology. In addition, there are several inhibiting factors, namely the difficulty of teachers in understanding the diversity of students' characters, the inadequate facilities and infrastructure of the automotive department, and the absence of conducive classroom conditions. This makes it difficult for teachers to adjust learning to the diversity of students' characters. However, the existing obstacles do not last long because at SMK Ma'arif NU Tirto Pekalongan, there is a collaboration with industry partners and assistance funds to complete the school's needs.